Analisis Prestasi Belajar Siswa MAS Al-Washliyah Parlakitangan Menggunakan Logika Fuzzy Tsukamoto Berdasarkan Nilai Rata-rata dan Absensi Siswa - Dea Tiara Azhari; Siti Ramadhani; Khairul Saleh (PT. Intelek Cendikiawan Nusantara, 2026)
Student achievement is an important indicator in assessing the success of the learning process in schools. Assessment of learning achievement is not only influenced by academic grades, but also by the level of student attendance during the teaching and learning process. This study aims to analyze student achievement at MAS Al-Washliyah Parlakitangan using the Tsukamoto Fuzzy Logic method by considering the average academic grade and student absences. The research method used is a quantitative approach with secondary data obtained from the school. The analysis stages include determining input and output variables, forming fuzzy sets and membership functions, compiling rule bases, inference processes, and defuzzification to produce crisp values. The input variables consist of average grades and student absences, while the output variable is student achievement. The results show that the Tsukamoto Fuzzy Logic method is able to provide a more objective assessment of learning achievement. Based on the defuzzification results, the student achievement score was 89.7, which is included in the good achievement category. Thus, the Tsukamoto Fuzzy Logic method can be used as a decision support system in evaluating student achievement and assisting schools in making more accurate and fair decisions.